Fall armyworm, Spodoptera frugiperda (J.E. Smith) damage on rice in the Philippines - Valdez, Evelyn M; Rillon, Genaro S.; Joshi, Ravindra; dela Cruz, Kennedy B.; Donayre, Dindo King M.; Martin, Edwin C.; Sandoval, Femia R.; Quilang, Eduardo Jimmy P.; Aquino, Minda Flor; Pascual, Maria Katrina; Jr, Jose Mariano; Aquino, Evergilio; Faheem, Muhammad; Annamalai, Sivapragasam (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2023)
Fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is a global invasive pest of corn, and is also common on sorghum, rice and millets, and is reported to be a larval host of 353 cultivated and uncultivated plants . FAW, a native to the tropical and subtropical regions of north, Central, and South America, continues to rapidly spread to Africa and Asia since 2016, threatening food security worldwide . In the Philippines, its first damage on corn was reported in June 2019 in Piat, Cagayan , while that on rice was in May 2021 in Gonzaga, Cagayan, and subsequently to other municipalities in Region 2 . Unlike corn, however, little is known about FAW damage and host preference for rice in the Philippines. Rice, a key food security crop for the Philippines and in Asia, is amongst the key host of the FAW elsewhere (e.g., USA) . The injury that the FAW will inflict in the rice plant should be known and assessed to quantify the potential yield losses, and predict when an intervention is necessary to avoid incurring potential yield losses. With this background, we conducted FAW monitoring and damage assessment in the areas reported to have FAW occurrence starting May 2021. During 2021 and 2022 assessment periods, monitoring was conducted during the months of May, June, and July. However, starting January 2023, the monitoring and damage assessments were conducted monthly with the exception for May and June wherein it was done weekly since these months coincided with the seedling stage of the rice in a majority of rice-growing areas in the Philippines and where FAW attack was reported during the previous years. FAW larval population and damage were assessed in rice seedbeds. The number of FAW larvae were counted and visual damage was estimated in a 1 m2 quadrat with three replicates.